DESAIN SISTEM IOT PADA SMART LOCK DOOR MENGGUNAKAN SENSOR GETAR - Rangga YP, M.; Ariyadi, Tamsir (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
The increasingly rapid development of the technological era makes human activities easier, technological advances not only offer aspects of convenience and practicality but one of the most important things is the security system. One of them is a smart lockdoor product that is here to provide a high level of security, namely an integrated intelligent automatic door lock system that not only provides safer security but also provides the necessary information. The electrical engineering laboratory is a place for students and lecturers to carry out learning and practicum activities, this room is to store all kinds of equipment used for learning electronics and microcontrollers. Laboratories are very often used for lectures and practicums, indicating that the laboratory space is very productive, so the doors in the laboratory will be very vulnerable to door break-ins, making it easier for theft. The door security system in the UBD electrical engineering laboratory is very important to protect important items, current mechanical progress. This that the system should be able to be checked remotely is a must to make things easier. Currently available locks have an inadequate level of security or are considered insufficiently protected, smart lockdoors are the key to developing useful and effective security systems based on the internet of things, a technology that allows devices to communicate with each other via the internet. The problem is that conventional door security systems that use padlocks cannot provide a complete sense of security because they cannot remotely monitor users of conventional door security systems which are not equipped with theft warning system precautions. Therefore, an internet of thought (IOT) based door security system was designed using the SW-420 vibration sensor, which is supported by installed features such as RFID, fingerprint sensor, vibration sensor, camera and notification system connected to the user's cellphone. As for the vibration sensor with the aim of increasing door security, this research succeeded in implementing a smart lockdoor system based on the Internet of Things (IoT) using the ESP 32 module. Through the use of IoT technology, this system allows users to control the door using a mobile device or device. others connected to the internet network. In system testing, it was found that this system was able to work well in locking and opening doors remotely with a fast response. Additionally, the system also has security features such as authentication which ensures only authorized users can access and control the door. Keywords: Smart Lock Door, Sw 420 Vibration Sensor, Selenoid Doorn door